2020
DOI: 10.3390/ijerph17228700
|View full text |Cite
|
Sign up to set email alerts
|

Low Tongue Strength and the Number of Teeth Present Are Associated with Cognitive Decline in Older Japanese Dental Outpatients: A Cross-Sectional Study

Abstract: To mitigate the impact of dementia, initiating early intervention is important. This study aims to investigate the associations between deterioration in oral function and cognitive decline in older outpatients whose oral health was maintained in the dental clinic. This study included 50 outpatients aged ≥65 years. We used the Japanese version of the Montreal Cognitive Assessment (MoCA-J) to assess cognitive decline. Oral function was evaluated by tongue pressure, masticatory performance, and swallowing ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
2
13
0
2
Order By: Relevance
“…As an indicator of oral frailty, the perceived chewing disability was slightly high in both the intervention (3.40) and control (3.75) groups, while the tongue pressure in the preliminary oral examination was very low in both the intervention (17.75) and control (17.78) groups. This coincides with the high risk of diaphragmatic spasm or aspiration pneumonia at a tongue pressure of 20 kPa in the elderly aged ≥ 65 years [ 45 ]. However, the increase in tongue pressure to 27.24 kPa in the intervention group after the 6-week OHEMA was proof of its positive effect, with a predicted effect of enhancing the SWAL-QoL.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…As an indicator of oral frailty, the perceived chewing disability was slightly high in both the intervention (3.40) and control (3.75) groups, while the tongue pressure in the preliminary oral examination was very low in both the intervention (17.75) and control (17.78) groups. This coincides with the high risk of diaphragmatic spasm or aspiration pneumonia at a tongue pressure of 20 kPa in the elderly aged ≥ 65 years [ 45 ]. However, the increase in tongue pressure to 27.24 kPa in the intervention group after the 6-week OHEMA was proof of its positive effect, with a predicted effect of enhancing the SWAL-QoL.…”
Section: Discussionmentioning
confidence: 62%
“…Oral frailty was assessed based on subjective oral dryness, perceived chewing disability, chewing disability, swallowing difficulty, and inconvenient pronunciation [ 28 , 29 ]; dietary factors (meal types, mealtimes, and daily amount of water); activities of daily living (ADL) [ 30 , 31 , 32 ] and instrumental activities of daily living (IADL) [ 33 ]; mini-mental state examination—Korean version (MMSE-K) [ 34 ]; the multidimensional scale of perceived social support (MSPSS) [ 35 , 36 ]; and oral health-related quality of life (OHRQoL) scales (oral health impact profile (OHIP-14), geriatric oral health assessment index (GOHAI), and SWAL-QoL) [ 37 , 38 , 39 , 40 , 41 , 42 ]. For oral health status, the number of remaining functional teeth, plaque index (PI) [ 43 ], tongue coating index [ 44 ], USFR [ 13 ], and tongue pressure [ 45 ] were measured. For intra- and inter-rater reliability, the authors conducted training before the beginning of the study and confirmed a concordance of > 90%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egashira et al [ 42 ] compared the oral function and environment of participants classified into healthy and MCI groups based on MoCA-J scores. They reported that the participants in the MCI group were significantly older than those in the healthy group and that the MCI group had significantly fewer existing teeth, significantly lower masticatory ability, and significantly lower maximum tongue pressure than the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…66 Cognitive decline was independently associated with lower tongue pressure. 67,68 Tongue pressure is an important indicator of tongue function. Tongue pressure was evaluated using a specified tongue pressure measurement device (JMS Co, TPM-01) 69,70 or the Iowa Oral Performance Instrument ® .…”
Section: Tong U Pre Ssure and Tong Ue Cle Aningmentioning
confidence: 99%